Exercise and Oxidative Damage in Nucleoid DNA Quantified Using Single Cell Gel Electrophoresis: Present and Future Application - Davison, Gareth W. (Frontiers in Physiology, 2016)
High intensity exercise can enhance the production of reactive oxygen and nitrogen free radical species, which may cause a number of perturbations to cellular integrity, including deoxyribonucleic acid (DNA) modification. In the absence of adequate DNA repair, it is theoretically possible that several biological disorders may ensue, in addition to premature ageing. This striking hypothesis and supposition can only be realised in the presence of sound methodology for the quantification of DNA damage and repair. The alkaline single-cell gel electrophoresis or ‘comet assay’ is a simple and reliable method for measuring the components of DNA stability in eukaryotic cells. The assay is commonly used in research associated with genotoxicology and in human bio-monitoring studies concerned with gene-environment interactions; but is currently less appreciated and under-utilised in the domain of exercise science. No exercise related study for example, has incorporated the comet assay combined with fluorescent in situ hybridisation methodology to detect and investigate whole genome, telomeric DNA, or gene region-specific DNA damage and repair in cells. Our laboratory and others have used the comet assay in conjunction with lesion-specific endonucleases to measure DNA strand breaks and oxidised bases to confirm that high intensity exercise can damage and destabilise DNA. Thus, the primary function of this review is to highlight recent advances and innovation with the comet assay, in order to enhance our future understanding of the complex interrelationship between exercise and DNA modification in eukaryotic cells. A brief synopsis of the current literature addressing DNA stability as a function of continuous aerobic exercise is also included.